PENTINGNYA MOTIVASI BELAJAR UNTUK MENINGKATKAN PRESTASI BELAJAR PADA SISWA DI SMP NEGERI 02 IV KOTO, LAMBAH, KABUPATEN AGAM - Muhammad Riski Munthe; Fenny Ayu Monia; Mirna Yesni (Universitas Pahlawan Tuanku Tambusai, 2023)
Motivation is very important in supporting a student's success. Moreover, currently the development of science and technology is increasingly sophisticated, making some students not care about their enthusiasm for learning and achieving. Especially when students enter their teens at the junior high school level. Individuals who become obstacles for students in learning and achieving are because they do not seek information and know the place to pass on their work and talents as well as their lack of desire to learn. In fact, the role and value of students' struggle as intellectuals has already been explained systematically. This also happens to students due to a lack of mastery of knowledge, direction, experience and motivation from their educators or what is usually referred to as teachers to their students. Writing this article aims to foster a growth mindset in students and educators or teachers that motivation and achievement are very important. Motivation as a main factor in learning functions to underlie, support and drive learning actions for students. The research was conducted using qualitative methods and descriptive observation. The results of this research show that student motivation and achievement are very important both in school and in everyday life. According to initial observation research, most students who have high learning motivation are students who are persistent in learning, do not give up easily and are able to solve the problems they face. On the other hand, students who have a low learning motivation score will feel normal about it, give up easily and are unable to focus on their work, making it difficult for students to learn and achieve.